Prevalence and course of strabismus through age 6 years in participants of the Early Treatment for Retinopathy of Prematurity randomized trial - VanderVeen, Deborah K. (2011)
PURPOSE: To present strabismus data for children who participated in the Early Treatment for Retinopathy of Prematurity (ETROP) randomized trial. METHODS: The prevalence of strabismus, categorized as present or absent, was tabulated for all children with history of high-risk prethreshold retinopathy of prematurity (ROP) who participated in the ETROP randomized trial and were examined at 9 months to 6 years of age. Relationships among strabismus and demographic measures, eye characteristics, and neurodevelopmental factors were analyzed. RESULTS: Among the 342 children evaluated at 6 years, the prevalence of strabismus was 42.2%. Even with favorable acuity scores in both eyes the prevalence of strabismus was 25.4%, and with favorable structural outcomes in both eyes the prevalence of strabismus was 34.2%. Of children categorized as visually impaired due to either ocular or cerebral causes, 80% were strabismic at the 6-year examination. Of 103 study participants who were strabismic at 9 months, 77 (74.8%) remained so at 6 years. Most strabismus was constant at both the 9-month (62.7%) and the 6-year examination (72.3%). After multiple logistic regression analysis, risk factors for strabismus were abnormal fixation behavior in one or both eyes (P < 0.001), history of amblyopia (P < 0.003), unfavorable structural outcome in one or both eyes (P = 0.025), and history of anisometropia (P = 0.04). Strabismus surgery was performed for 53 children. By 6 years, the cumulative prevalence of strabismus was 59.4%. CONCLUSIONS: Most children with a history of high-risk prethreshold ROP develop strabismus at some time during the first 6 years of life.